Search for associated Higgs boson production using like charge dilepton events in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Strauss, M.; et al. (Amer Physical Soc, 2011)
We present a search for associated Higgs boson production in the process p (p) over bar -> W/ZH -> l(+/-)l'(+/-) + X in ee, e mu, and mu mu final states. The search is based on data collected by the D0 experiment at the Fermilab Tevatron Collider at root s = 1.96 TeV corresponding to 5.3 fb(-1) of integrated luminosity. We require two isolated leptons (electrons or muons) with the same electric charge and additional kinematic requirements. No significant excess above background is observed, and we set 95% C. L. observed (expected) upper limits on ratio of the production cross section to the standard model prediction of 6.4 (7.3) for a Higgs boson mass of 165 GeV and 13.5 (19.8) for a mass of 115 GeV.